2011
DOI: 10.1007/s12088-011-0163-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Biotechnology in the Treatment of Polyester Fabric

Abstract: Poly (ethylene terephthalate) fibre [PET] is the commonly used fibre for majority of end-use applications, however, the desire for improved textile properties such as wettability or hydrophilicity are increasing. Biotechnology can be defined as the application of scientific and engineering to the processing of materials by biological agents to provide goods and services. The environmental issues associated with the textile processing are not new. Currently and in the years to come, besides lower cost of opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…The chemical process is the most common way of improving the surface characteristics of fabrics. But in recent years, different alternative eco-friendly processes are being tried, seeking to decrease the use of chemicals [2][3][4] . Between these processes, advanced plasma processing has been highlighting as a dry treatment and green technology that allows modifications at the micro/nanoscale of heatsensitive materials such as textiles [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…The chemical process is the most common way of improving the surface characteristics of fabrics. But in recent years, different alternative eco-friendly processes are being tried, seeking to decrease the use of chemicals [2][3][4] . Between these processes, advanced plasma processing has been highlighting as a dry treatment and green technology that allows modifications at the micro/nanoscale of heatsensitive materials such as textiles [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…A woven plain Polyester fabric was used with Ends/cm and picks/cm are 21 and weight fabric 132 g/m 2 . The weft and warp are made of polyester spun yarns.…”
Section: Methodsmentioning
confidence: 99%
“…Various approaches used in the modification of Polyester fabrics, modifying agents used, and application of the modified products based on the properties obtained have been investigated [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 4B-D shows the presence of hemispherical holes and cracks in the surface of polyester which increases the surface area for absorption of water molecules and ink trapped (Wavhal & Balasubramanya, 2011). It was shown that the damage after biodegradation by enzyme or microorganisms was apparent as cracks and holes in the polyester fibres improve water penetration and the absorbent properties of regular polyester fabric.…”
Section: Sem Study Of the Fabricsmentioning
confidence: 97%